The Influence of Shepherd Leadership Based on 1 Timothy 3:1-6 on the Spiritual Growth of Congregants in the Gereja Kristen Kudus Indonesia (GKKI) in Jabodetabek - Sunardi, Philipus (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
This research highlights the significance of leadership in the spiritual growth of the congregation within the context of the Indonesian Christian Holy Church (GKKI) in Jabodetabek. The correlation analysis results indicate that Shepherd Leadership holds a substantial relationship with Spiritual Growth (correlation coefficient = 0.693, Sig < 0.1). These findings demonstrate that the comprehension and execution of vision and mission by a spiritual leader have a considerable impact on enhancing the quantity of faith among the congregation. This study suggests that spiritual leaders need to have a thorough understanding of their roles and responsibilities in order to lead effectively, mitigate conflicts, and shepherd competently. Furthermore, the research findings shed light on challenges faced by the congregation, such as difficulties in spiritual growth. This research makes a significant contribution to understanding the dynamics of spiritual leadership within the GKKI context in Jabodetabek.